Maqasid Syariah's Persp ective on Premarital Health Guidance in Pasangkayu District - laodemuhamadsaefudin; Abidin, Abidin; Muhammad Akbar; Basrin Ombo (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC LAW AND SOCIETY, 2024)
The requirement to carry out premarital health tests has been regulated in the Joint Instruction of the Director General of Islamic Community Guidance and Hajj Affairs, Department of Religion and the Director General of Eradication of Infectious Diseases and Environmental Health for Settlements, Department of Health No. 02 of 1989 concerning Tetanus Toxoid (TT) Immunization for Bride and Groom Candidates. Health tests are defined as tests carried out before carrying out the wedding. The research aims are: (1) to analyze the implementation of premarital health guidance in Pasangkayu District; (2) To analyze premarital health guidance from a maqasid sharia perspective in Pasangkayu District. This research uses qualitative methods with data collection techniques: observation, interviews, and documentation. Researchers use data analysis techniques, such as data reduction, presentation, verification, and conclusion. Research Results: (1) The essence of premarital health guidance is preventive measures to avoid health problems that will occur to oneself, one's partner, and offspring. (2) If viewed from the maqasid sharia perspective of Imam Syatibi, it is at the level of maqasid hajiyati or secondary needs, namely, if you do not carry out a health check, it will not cause damage. Still, it could be a dharuriyat if your partner's health check occurs.